2019
DOI: 10.33899/ijvs.2019.163167
|View full text |Cite
|
Sign up to set email alerts
|

The effect of pisang ambon (Musa paradisiaca L.) stem extract on the regulation of IL-1ß, IL-6 and TNF-α in rats’ enteritis

Abstract: Considering that NSAIDs are widely used in medication for pain, inflammatory, and fever, its side effect, mucosal erosion, needs to be minimized. The purpose of this paper is to study the potential use of Musa paradisiaca L. stem extract in lowering TNFα, IL-1ß and IL-6 proinflammatory cytokines in rats' enteritis. Thirty male wistar strain rats (Rattus Norvegicus) aged 2-3 months were divided into 5 groups with 6 repetitions. The positive and negative control groups were given a solvent of Musa paradisiaca L.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 8 publications
1
1
0
2
Order By: Relevance
“…The earliest expression of both mediators was noticed in 30 min antemortem wound time, whereas the reactivity increased at 180 min and peaked at 360min. Our results agree with the previous findings where it was observed that increased expression of the IL-6 and TNF-α markers is related to the time of injury (38,4,(39)(40)(41).…”
Section: Discussionsupporting
confidence: 93%
“…The earliest expression of both mediators was noticed in 30 min antemortem wound time, whereas the reactivity increased at 180 min and peaked at 360min. Our results agree with the previous findings where it was observed that increased expression of the IL-6 and TNF-α markers is related to the time of injury (38,4,(39)(40)(41).…”
Section: Discussionsupporting
confidence: 93%
“…Serbuk H. athra dilarutkan dengan pelarut n-heksana selama 24 jam. Maserat yang diperoleh ditampung dan diuapkan menggunakan rotary evaporator dimasukkan ke dalam wadah kedap udara dan disimpan dalam lemari es sampai akan digunakan (8,11) .…”
Section: Preparasi Dan Ekstraksiunclassified
“…Hal tersebut tidak diregistrasi oleh food and drug administration (FDA) untuk digunakan pada banyak spesies. Penggunaan aspirin pada hewan secara primer berdasarkan empiric dari data yang dipublikasikan (Papich, 2016) (Kurnijasanti, 2019).…”
Section: Pendahuluanunclassified